Stratified Analysis of the Assessment of Human Development in Iraq - Salman , Faez Hamid (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to reach the best distinction function for the variables that have common characteristics and characteristics to distinguish between groups, in order to identify the conditions of governorates that suffer from the problem of deprivation, which allows the interested parties and regulatory bodies to intervene to take corrective measures, and the main indicators of the deprivation guide have been adopted and included (Education, health, infrastructure, housing, protection) based on the 2010 data available in the Central Bureau of Statistics.